Coordinated perimeter control of urban road network based on traffic carrying capacity model - Gao, Yuhong (2023)
The perimeter traffic control of urban road network is of great significance for alleviating traffic congestion. Most of the existing perimeter control methods are design schemes based on macroscopic fundamental diagram (MFD), accompanied by effective algorithmic techniques. However, when applying MFD-based models for perimeter traffic control, it is always restricted by the heterogeneity of road network. In response to this problem, it is urgent to find a new model, which can not only get rid of the influence of heterogeneity, but also describe the evolution of traffic flow to guide the perimeter control. Research displays that the road network traffic carrying capacity model, a model designed to calculate the maximum number of vehicles in the road network under a certain service level, can meet these requirements. First, through the theoretical demonstration of the mathematical model, it is proved that the network heterogeneity neither affects the existence of traffic carrying capacity nor changes its parameter value. This further clarifies that there is no need to divide the homogeneous sub-regions in the preliminary steps of the proposed perimeter control. Second, an innovative road network perimeter coordination control framework is developed, which has a simple operation process and high computational efficiency. The main components of the structural framework include data collector, sub-region coordination controller, and perimeter signal controller. In particular, the core idea of coordinated control is to adjust and model the distribution mode of vehicles in the road network through the transfer of traffic flow between sub-regions, thereby achieving the optimal operation efficiency of the transportation system. Finally, the SUMO simulation software is employed to verify and evaluate the proposed model. The results show that compared with the no perimeter control and the MFD-based perimeter control, the proposed perimeter control strategy is demonstrated to have impressive performance. A key advantage is that the application of the proposed approach does not need to consider the road network heterogeneity, and has great results in both non-congested and congested conditions. Findings from this study can provide a novel direction for the application of urban regional traffic control.